2021
DOI: 10.3389/fcomm.2021.628780
|View full text |Cite|
|
Sign up to set email alerts
|

Vowel Quality and Direction of Stress Shift in a Predictive Model Explaining the Varying Impact of Misplaced Word Stress: Evidence From English

Abstract: The use of suprasegmental cues to word stress occurs across many languages. Nevertheless, L1 English listeners' pay little attention to suprasegmental word stress cues and evidence shows that segmental cues are more important to L1 English listeners in how words are identified in speech. L1 English listeners assume strong syllables with full vowels mark the beginning of a new word, attempting alternative resegmentations only when this heuristic fails to identify a viable word string. English word stress errors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 61 publications
(133 reference statements)
0
8
0
Order By: Relevance
“…Given that the focus of this study was to investigate the relationships among the four skills, the time allocated to vocabulary was given to speaking and reading skills. Moreover, because pronunciation has a crucial role in identifying word boundaries in connected speech (Cross, 2009) and in enhancing intelligibility and comprehensibility (Ghosh & Levis, 2021) in speaking, the time assigned to this subskill was given to both speaking and listening skills. Furthermore, Richards (2015) has referred to the pivotal role of grammar in writing proficiency and speaking accuracy; therefore, the time spent on grammar activities was given to both writing and speaking.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the focus of this study was to investigate the relationships among the four skills, the time allocated to vocabulary was given to speaking and reading skills. Moreover, because pronunciation has a crucial role in identifying word boundaries in connected speech (Cross, 2009) and in enhancing intelligibility and comprehensibility (Ghosh & Levis, 2021) in speaking, the time assigned to this subskill was given to both speaking and listening skills. Furthermore, Richards (2015) has referred to the pivotal role of grammar in writing proficiency and speaking accuracy; therefore, the time spent on grammar activities was given to both writing and speaking.…”
Section: Resultsmentioning
confidence: 99%
“…(10 of 19) | and in enhancing intelligibility and comprehensibility (Ghosh & Levis, 2021) in speaking, the time assigned to this subskill was given to both speaking and listening skills. Furthermore, Richards (2015) has referred to the pivotal role of grammar in writing proficiency and speaking accuracy; therefore, the time spent on grammar activities was given to both writing and speaking.…”
Section: Writing and Grammar 14%mentioning
confidence: 99%
“…Researchers have shown that effective communication may not be intelligible without correct stress (Kang et al, 2010;Kenworthy, 1987). Incorrect stress sometimes hinders intelligibility and comprehensibility at word and sentence levels (Gallego, 1990;Ghosh & Levis, 2021;Jenkins, 2002). Grosjean & Gee (1987) aver that lack of intelligibility occurs because of listeners' overreliance on word stress to decode unfamiliar words.…”
Section: Importance Of Stressmentioning
confidence: 99%
“…Both Ghosh and Levis (2021) and Liu and Reed (2021) found L1 and L2 differences. The former identified a lower baseline and greater variation related to lexical stress errors in L2 listeners compared to L1 listeners.…”
mentioning
confidence: 90%